GESTATIONAL DIABETES MELLITUS: MODERN GLYCEMIA MONITORING SYSTEMS - YU.A. DUDAREVA; V.A. GURYEVA; G.V. NEMTSEVA (Avicenna Tajik State Medical University, 2022)
This review evaluates the role of continuous glucose monitoring (CGM) during pregnancy in women with gestational diabetes mellitus (GDM). Globally, GDM has been associated with an increased risk of adverse maternal and fetal health outcomes. It has been shown that currently existing methods of glycemic control in patients with GDM do not always provide adequate assessment of daily glycemic variability, and, unfortunately, the incidence of obstetric complications and diabetic fetopathy does not decrease. The system of CGM is a rather promising method which makes it possible to effectively assess the daily variability of glycemia, to detect high levels of postprandial glycemia and nocturnal hypoglycemia.